DIRECTORS' RESPONSIBILITIES AS LIQUIDATORS IN THE DISSOLUTION OF LIMITED LIABILITY COMPANIES - Anak Agung Sagung Nadya Prabandari; I Gede Yusa (Transpublika Publisher, 2024)
This article aims to examine the legal regulations regarding the responsibilities of directors as liquidators in the dissolution of limited liability companies. This journal article employs a normative legal research method that utilizes legislative and conceptual approaches by reviewing the Limited Liability Company Law. The regulations for the dissolution of limited liability companies are outlined in the Company Law Article. The dissolution of a company must be followed by liquidation carried out by a liquidator. In terms of appointing a liquidator, the Company Law only provides for the appointment of a liquidator similar to the general appointment of directors. This provision of the Company Law does not necessarily provide legal certainty for creditors or interested parties. Based on this, the issues can be raised regarding how the legal certainty of the regulation of Directors as Liquidators in the dissolution of Limited Liability Companies is established, as well as what the Responsibilities of Directors as Liquidators are in the presence of conflicts of interest within Limited Liability Companies.